Global social policy international organizations and the future of welfare - Deacon, Bob; Hulse, Michelle; Stubbs, Paul 1959- (SAGE Publications Ltd, 1997)
Global Social Policy looks at the impact of the globalization process on social policy. National social policy is increasingly determined by global economic competition and international organizations. Its substance is becoming more transnational and now has to be understood in terms of global social redistribution, social regulation, social provision, and empowerment. This book examines trends in global inequity and summarizes the diverse experiences of different welfare regimes across the world. The authors review the social policies of international organizations such as the World Bank, the International Monetary Fund, UN agencies, and the European Union, and show them to be engaged in heated controversy regarding the future for welfare. They argue that this concealed global discourse needs to be brought into an accountable arena. Global Social Policy will be invaluable reading for students and academics in social policy, international relations, political science, and development studies.